The Cursed Moon - Cervantes, Angela (New York : Scholastic Press, 2023)
"Rafael Fuentes isnt easily scared. He loves writing ghost stories, reading scary books, and entertaining his friends with terrifying tales he creates on the spot. Rafa has come up against enough real-life scary situations that fictional hauntings seem like no big deal. As an eerie blood moon hangs in the sky one night, Rafa tells a group of friends about the Caretaker. The Caretaker is an evil ghost who lures unsuspecting kids into the neighborhood pond... and they dont ever come out. Rafa is really proud of his latest creation, until strange things start to happen around him. With a sinking feeling, Rafa figures out the Caretaker is real. Rafa has brought the ghost to life-and only he can stop him."--
Keywords: Hispanic American families -- Juvenile fiction; Authors -- Juvenile fiction; Children of prisoners -- Juvenile fiction; Fear -- Juvenile fiction; Hispanic American families -- Fiction; Authors -- Fiction; Children of prisoners -- Fiction; Fear -- Fiction; Junior Fiction; Ghost stories; Paranormal fiction; Horror fiction